Combined use of charcoal, sago bark ash, and urea mitigate soil acidity and aluminium toxicity - Hamidi, Nur Hidayah (Multidisciplinary Digital Publishing Institute, 2021)
Highly weathered tropical acidic soils are characterized by low pH, low organic matter, and aluminium and iron toxicity. These factors pose a challenge to achieving sustainable agriculture. The continued increase in the human population with the accompanied increasing food demand have negatively impacted the global N cycle partly because of excessive use N fertilizers particularly urea which is commonly used in agriculture. Ammonia volatilization from urea as an example, negatives the environmental quality. This study focuses on soil-N availability, pH, exchangeable acidity, Al3+, and H+ of a highly weathered acid soils (Bekenu series) through the combined use of charcoal, sago bark ash, and urea. To this end, an incubation study was conducted for 90 days through the combined use of charcoal, sago bark ash, and urea to determine if this approach could improve soil N availability and pH at the same time reducing exchangeable acidity, and Al3+, and H+ toxicity. The amount of urea used was fixed at 100% as the recommended rate. Charcoal and sago bark ash were varied by 25%, 50%, 75%, and 100%, respectively of the recommended rate. Selected soil physico-chemical properties were determined using standard procedures. This study revealed that combined use of charcoal, sago bark ash, and urea increased soil pH and base cations simultaneously the approach also reduced exchangeable acidity, exchangeable Al3+, and exchangeable H+. There were no significant differences in soil total N, exchangeable NH4+, and available NO3− for the combined use of charcoal, sago bark ash, and urea and urea alone because of the acid neutralizing effect of the amendments. Apart from the sago bark ash’s liming effect, the high affinity of the functional groups of the charcoal for Al3+ might have impeded Al3+ from undergoing hydrolysis to produce more H+ because a complete one mole of Al3+ hydrolysis produces three moles of H+. Thus, the combined use of charcoal and sago bark ash can mitigate soil acidity and aluminium toxicity, although this approach has minimal effect on-N.